2016
DOI: 10.5507/bp.2016.027
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of MYB gene breaks in adenoid cystic carcinoma of the salivary glands and its prognostic significance

Abstract: , Ivo Starek aAims. To detect MYB gene breaks in adenoid cystic carcinoma (ACC) of the salivary glands and its correlation with prognosis and selected clinical parameters Methods. MYB gene break was detected by FISH assay in 23 adenoid cystic carcinomas using formalin-fixed paraffinembedded blocks. The Kaplan-Meier survival analysis was used to estimate prognosis. Results. Fifteen of 23 evaluated tumours were MYB positive and 8 MYB negative. The 10-year cumulative survival, respectively disease free interval, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
2
6
1
Order By: Relevance
“…Six articles scoring seven or more stars on the NOS were included in the sensitivity analysis, and only outcomes that were observed in two or more studies were included in this analysis. 12,17,18,21,23,24 The results of the sensitivity analysis were in accordance with the previous results, and no significant difference was observed in any outcome, showing that patients who were MYB positive did not have poorer overall prognoses on sensitivity analysis (Supplementary Table 1). Figure 5 shows a funnel plot of all the included outcomes in this meta-analysis.…”
Section: Sensitivity Analysis and Publication Biassupporting
confidence: 88%
See 2 more Smart Citations
“…Six articles scoring seven or more stars on the NOS were included in the sensitivity analysis, and only outcomes that were observed in two or more studies were included in this analysis. 12,17,18,21,23,24 The results of the sensitivity analysis were in accordance with the previous results, and no significant difference was observed in any outcome, showing that patients who were MYB positive did not have poorer overall prognoses on sensitivity analysis (Supplementary Table 1). Figure 5 shows a funnel plot of all the included outcomes in this meta-analysis.…”
Section: Sensitivity Analysis and Publication Biassupporting
confidence: 88%
“…West et al 15 demonstrated that ACC with MYB translocation had a trend towards higher local relapse rates, although these results were not statistically significant. Broz et al 17 found a tendency towards prolonged survival in patients with ACC who were MYB negative; however, the difference was not statistically significant either. Mitani et al 18 reported that high MYB protein expression was related to worse prognosis for ACC; however, von HSL et al 18 found no direct correlations between MYB protein expression and ACC prognosis.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, unlike the CRTC1‐MAML2 fusion in mucoepidermoid carcinoma, the significance of the MYB‐NFIB fusion remains unclear. A handful of studies suggest that the MYB‐NFIB rearrangement is associated with improved survival . However, other studies show no survival benefit, while others still report a survival disadvantage .…”
Section: Resultsmentioning
confidence: 99%
“…Adenoid cystic carcinoma (ACC) is a rare malignancy that is able to exist at various sites within the body, although it is most commonly localized to the salivary gland (1). Salivary ACC displays characteristic features, including biological behavior diversity and histological heterogeneity (2). Patients diagnosed with salivary ACC usually present with a poor prognosis due to metastasis to distant organs, the high risk of relapse and the propensity of the tumor to invade the peripheral nerves.…”
Section: Introductionmentioning
confidence: 99%